THE BOREAL-TETHYAN BIOGEOGRAPHICAL MOLLUSC ECOTONE IN EUROPE DURING THE JURASSIC-CRETACEOUS TRANSITION (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
Late Jurassic and earliest Cretaceous molluscs of the northern hemisphere were distinctly differentiated geographically into Boreal taxa, usually north of 50° N, and Tethyan taxa, usually south of 45° N. Between these latitudes certain areas were displaced from time to time, although the biogeographical ecotone was stable. The magnitude of the ecotone and the migration of molluscs inside the ecotone varied in time and space, in direction (unidirectional and bidirectional) and intensity (expansion and "isolate straying"). The frequency of the Boreal-Tethyan migrations of molluscs is explained by eustacy and by geographical barriers existing between the Northern Caucasus and Middle-Russian basins.